Apparent rarity of asymptomatic herpes cervicitis in a woman with intra-uterine contraceptive device (2013)
Infection with genital herpes simplex virus (HSV) remains a common viral sexually transmitted disease, often subclinical and a major worldwide problem of women of reproductive age group. Herpes cervicitis is an unusual presentation of Herpes simplex virus infection in females. The finding of herpes cervicitis on routine pap smear of an asymptomatic woman on Intrauterine contraceptive device still further supports the need for increased awareness on the possibility of Herpes simplex virus infection among women, particularly those on Intrauterine contraceptive device. The index case is a 28 years old Nigerian female who was referred to our Special Treatment Clinic on account of an abnormal pap smear cytology which was in keeping with Herpes cervicitis. There was no history of genital ulcer in this patient; however ELISA for HSV 2 IgM was positive in her. We therefore describe a case of herpes cervicitis in an asymptomatic woman on intrauterine contraceptive device. This case highlights to clinicians the need to be aware of the possibility of this association and to carry out relevant investigations so as to identify and treat these patients appropriately. Therefore, there is a need to put in place adequate public health intervention strategy to prevent genital herpes in women of reproductive age group with a view to preventing the possibility of congenital herpes in subsequent pregnancy.